Homophobic Bullying: An International View - Sánchez Sibony, Adrian; Ortega Ruiz, Rosario; Casas , José A. (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2018)
Homophobic school bullying, affective-sexual diversity and whereby intolerance and rejection towards this diversity have been a research focus over the last decade. The present research paper aims to systematically review the international bibliography that covers the homophobic school bullying attitudes from different viewpoints. The discussion on the singularity of this type of unjustified aggression remains open. Thus, this paper attempts to research the conceptual meaning of this phenomenon and contribute with indicators that allow a better approximation to it.